The EDEN ISS Antactic Greenhouse Project - 9 Month Mission Status after Deployment in Anatctica - Schubert, Daniel; Zeidler, Conrad; Bamsey, Matthew; Vrakking, Vincent; Zabel, Paul; Kohlberg, Eberhard (2018)
Sustained human presence in space requires the development of new technologies to maintain environment control, to provide water, oxygen, food and to keep astronauts healthy and psychologically fit. The cultivation of higher plants can contribute to all major aspects within biological life support systems and hits psycho-physiological impact on the crew well being, also represents an all-in-one-approach, not accomplished by any single physical/chemical system. The international EDEN ISS project aims to develop and validate technologies as well as investigate food safety and plant handling procedures for higher plant cultivation. A dedicated greenhouse module called the Mobile Test Facility was built by an international consortium within the European Horizon 2020 framework. The EDEN ISS consortium focused on advancing controlled environment agriculture technologies and adjoining research fields for safe food production in closed-loop space systems such as planetary habitats and transfer vehicles. A key element of the project is the testing of the greenhouse system during an analogue mission at the Neumayer Station III in Antarctica. In addition to advancing hardware for space insight, the facility provides the overwintering Neumayer Station III crew of 10 people with fresh vegetables. The paper presents the current mission status (after 9 months) of the EDEN ISS mission.